Lung and Abdominal Biopsies in the Age of Precision Medicine - Dalag, Leonard; Fergus, Jonathan K.; Zangan, Steven M. (Seminars in Interventional Radiology, 2019)
Image-guided percutaneous needle biopsies (PNBs) are one of the most common procedures performed in radiology departments today. Rapid developments in precision medicine, which identifies molecular and genomic biomarkers in cancers, have ushered a new paradigm of oncologic workup and treatment. PNB has conventionally been used to establish a benign or malignant nature of a lesion during initial diagnosis or in suspected metastatic or recurrent disease. However, increasing amounts of tissue are being required to meet the demands of molecular pathologic analysis, which are now being sought at multiple time points during the course of the disease to guide targeted therapy. As primary providers of biopsy, radiologists must be proactive in these developments to improve diagnostic yield and tissue acquisition in PNB. Herein, we discuss the important and expanding role of PNB in the age of precision medicine and review the technical considerations of percutaneous lung and intra-abdominal biopsy. Finally, we examine promising state-of-the-art techniques in PNB that may safely increase tissue acquisition for optimal molecular pathologic analysis.
Keywords: interventional radiology; precision medicine; biopsy; percutaneous